Women empowerment through involvement in community-based health and nutrition interventions: Evidence from a qualitative study in India. - Manas Ranjan Pradhan; Sayeed Unisa; Ramu Rawat; Somila Surabhi; Abhishek Saraswat; Reshmi R S; Vani Sethi (PLoS ONE, 2023)
Women's empowerment is fundamental for realizing unalienable human rights and is vital to sustainable development outcomes. In India, the SWABHIMAAN intervention program was an integrated multi-sectoral strategy to improve girls' and women's nutrition before conception, during pregnancy, and after childbirth. This study assesses the role of self-help-group (SHGs) in improving the effectiveness of community health interventions and its impact on their self-empowerment. Qualitative data gathered through in-depth interviews (IDI) with community-based SHG members involved as Nutrition Friend (Poshan Sakhi-PS) in the SWABHIMAAN program in 2018 was used for analysis. Informed consent procedures were followed, and only those who voluntarily consented to the interview were interviewed. Twenty-five IDIs of purposively selected PSs in three states (Bihar, n = 9; Chhattisgarh, n = 8; and Odisha, n = 8) were analyzed thematically, according to Braun & Clarke (2006). NVivo 12 software was used for organizing and coding data. Three central themes that emerged to explain women's empowerment were (1) Barriers & redressal mechanisms adopted by PS, (2) PS as a change-maker, and (3) Changes in the life of PS. The study found that women perceive themselves as more empowered through involvement in the SWABHIMAN intervention program, besides improving the community's and their households' nutritional status. The results suggest that policies and programs on health and nutrition interventions need to involve peer women from the community, leading to more effective outcomes. Empowering women and closing gender gaps in employment/work are critical to achieving the 2030 Sustainable Development Goals.